Copper‐Catalyzed Asymmetric Conjugate Addition of Dimethylzinc to Acyl‐N‐methylimidazole Michael Acceptors: Scope, Limitations and Iterative Reactions. Issue 15 (1st August 2016) - Drissi‐Amraoui, Sammy; Schmid, Thibault E.; Lauberteaux, Jimmy; Crévisy, Christophe; Baslé, Olivier; de Figueiredo, Renata Marcia; Halbert, Stéphanie; Gérard, Hélène; Mauduit, Marc; Campagne, Jean‐Marc
Abstract: An efficient copper‐catalyzed enantioselective conjugate addition of dimethylzinc to unsaturated 2‐acyl‐ N ‐methylimidazoles has been achieved using a chiral bidentate hydroxyalkyl‐NHC ligand. The reactions proceed with excellent regioselectivity (1, 4 vs . 1, 6 and 1, 8) in extended conjugated systems to afford the 1, 4‐adducts in high enantioselectivities. This regioselectivity could be ascertained by DFT studies highlighting the crucial role of the imidazole ring. Thanks to the development of efficient protocols to regenerate the unsaturated 2‐acyl‐ N ‐methylimidazole moiety, an iterative process has been developed ultimately leading to 3, 5, 7 all‐syn or anti‐anti polydeoxypropionate stereodiads. Abstract :